The Paradox of Digital Electoral Governance: The Role of SILON-SIPOL-SIREKAP in Indonesia’s Electoral Accountability - Albahori Albahori; Sunarto Sunarto; Gatot Hery Djatmika; T. Herry Rachmatsyah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study examines Indonesia's digital electoral governance systems—SILON, SIPOL, and SIREKAP—designed to uphold the constitutional principles of direct and fair elections (LUBER-JURDIL). SILON demonstrated an efficiency of 80% in processing candidate lists, achieving 30% compliance with female representation. SIPOL reduced administrative errors by 40%; however, systemic challenges remain. SIREKAP encountered a 12% discrepancy in vote recapitulation in rural areas such as Ogan Komering Ilir, mainly due to offline data entry bottlenecks (KPUD Sumsel, 2024). These issues illustrate Heeks' (2001) concept of the